Contribution of the Implementation of High-Touch Teachers and the Academic Self Concept of Student Learning Motivation In Mathematics Subject - Septia Ningsih; Marjohan Marjohan; Herman Nirwana (International Journal of Research in Counseling and Education, 2019)
This study motivated by the low level of student motivation in mathematics subjects. The application of high-touch teachers and academic self-concept are factors that influence students' learning toward motivation in mathematics subjects. This study uses a descriptive correlational quantitative method. The population of this study was all students of MAN 1 Pekanbaru totalling 1138 and 322 students were selected by using proportional stratified random sampling. The instruments used were questionnaires for the application of high scored teachers’, academic self-concept, and student learning motivation in mathematics subjects using a model Likert scale. The findings of the study were the application of high touch teachers in a good category, academic self-concept was in a fairly positive category, student motivation in mathematics subjects was in the high category, the application of high touch teachers and academic self-concept respectively contributes significantly positively to students' learning motivation on mathematics subjects.